Impact of Citizen Attitudes on the Socio-Environmental Management of the Coastal Defense (Journal on studies and research of academic knowledge, 2026)
Riverside cities have historically faced high levels of vulnerability to flooding due to their location on floodplains—a situation increasingly intensified by the effects of climate change. In this context, coastal defenses have become strategic infrastructure for mitigating hydrological risks. However, their effectiveness depends not only on technical factors but also on citizens’ attitudes toward socio-environmental management. This study aimed to analyze the impact of such attitudes on the sustainability of coastal defenses. To achieve this, a systematic literature review was conducted, focusing on studies published between 2019 and 2025 in academic repositories such as Scopus, Web of Science, SciELO, Redalyc, and Google Scholar. Inclusion criteria prioritized peer-reviewed publications addressing citizen participation, community resilience, and socio-environmental governance in flood-risk contexts. The results show that risk perception, institutional trust, community co-responsibility, and social equity are decisive factors for the social appropriation and effectiveness of coastal defenses. Moreover, international experiences confirm that integrating local knowledge, environmental education, and participatory governance strengthens community resilience. It is concluded that the socio-environmental management of coastal defenses requires the articulation of technical solutions with processes of education, institutional transparency, and citizen co-responsibility to ensure long-term sustainability. Future studies should deepen the analysis of local attitudes through empirical methodologies, exploring the relationship between social vulnerability and community resilience in riverside contexts.
Keywords: Citizen attitudes; Socio-environmental management; Coastal defense; Community resilience